Education As An Inducement For Change And Sustainable Development - Shekhawat, Vishakha (Trinity Law Review, 2023)
Education enables people to develop awareness of themselves, their environment and encourage them to play their social role at work and in the community. The right to education was first enshrined in the Universal Declaration of Human Rights in 1948. Ensuring that all people are afforded a high standard of education and improving education will be reaffirmed as a key global goal of development under the post-2015. “High quality education and lifelong learning” and the capacity of teachers are the key factors in empowering youth as a “globally connected engine for change”. UNESCO of the International Commission on Education for the twenty-first century highlighted the importance of education in supporting human development. “The commission does not see education as a miracle cure or a magic formula opening the door to a world in which all ideals will be attained, but as one of the principal means available to foster a deeper and more harmonious form of human development and thereby to reduce poverty, exclusion, ignorance, oppression and war”.
Keywords: Education 2030 agenda; SDG; education; human development; sustainable development; UNESCO of the International Commission on Education for the twenty-first century